Migraine and tension-type headache in Germany. Prevalence and disease severity from the BURDEN 2020 Burden of Disease Study - Michael Porst; Annelene Wengler; Janko Leddin; Hannelore Neuhauser; Zaza Katsarava; Elena von der Lippe; Aline Anton; Thomas Ziese; Alexander Rommel (Journal of Health Monitoring, 2020)
Headache disorders are widespread among women and men in Germany and are primarily associated with restrictions on quality of life. The two most common types of headache disorders are migraine and tension-type headache. In order to gain valid estimates of the prevalence of these conditions, a cross-sectional telephone-based survey was conducted among adults in Germany (N=5,009) between October 2019 and March 2020. The frequency, duration, the characteristics and comorbidities associated with headache were measured using the diagnostic criteria defined in the International Classification of Headache Disorders. 57.5% of women and 44.4% of men in Germany stated that they had had a headache in the last twelve months. 14.8% of women and 6.0% of men meet all of the diagnostic criteria for migraine. Tension-type headache affects 10.3% of women and 6.5% of men. Migraine and tension-type headache are predominantly found among people of working age and steadily decrease with age. Migraine is often accompanied by comorbidities such as depressive symptoms and anxiety disorders. People affected by headache disorders tend to receive very little professional medical care, with only a minority seeking treatment within a year. These results provide a comprehensive picture of the population-related impact of headache disorders and are used in the BURDEN 2020 study to quantify key indicators for burden of disease assessment.